Reflections on a peer-led Writing Café - Emily Webb; Felicity Edwards; Zoe Harrington; Eve Middleton; Amy Somekh; Tharushi Wijesiriwardena (Journal of Learning Development in Higher Education, 2023)
Academic writing can often be a solitary, even isolating, experience for students. For those new to UK higher education institutions, as well as those seeking to develop their academic skills, academic writing can be a daunting task. Supporting students with academic writing is a significant element of the work of the Learning Development team at the University of Leeds. Established methods of support, including co-curricular and embedded workshops, online resources, and one-to-one appointments, are effective, but they do little to promote a sense of community or belonging. Instead, the power dynamic between student and learning advisor remains very similar to the one students experience with academic staff. Peer support has proved to be a powerful tool in learning development, especially in academic writing (Longfellow et al., 2008; Pritchard, 2015; Tamachi et al., 2018). Building on the successes of PASS/PAL schemes and peer-led support at other institutions, the LD team at Leeds opened a Writing Café in October 2022 to support undergraduate students in the development of their academic writing. Led by five student ‘academic writing mentors’, the Writing Café offers an opportunity for undergraduates to have a less isolating experience of writing while building their communities and networks within the institution.